2012
DOI: 10.11613/bm.2012.038
|View full text |Cite
|
Sign up to set email alerts
|

Serum thyroglobulin antibody levels within or near to the reference range may interfere with thyroglobulin measurement

Abstract: High concentration of thyroglobulin antibodies (TgAb) is a major limiting factor of thyroglobulin measurements in patients with differentiated thyroid cancer. We investigated whether thyroglobulin antibody added to serum samples could interfere with the thyroglobulin assay. Thyroglobulin levels in serum samples with different concentrations of thyroglobulin were measured by electrochemiluminescence immunoassay before and after the addition of increasing concentrations of thyroglobulin antibody using the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Data found in the literature indicated that in the presence of TgAb, values of Tg determined by immunoradiometric assay are usually lower than real values, even if the concentrations of TgAb are very low [5, 9, 19]. In previous reports, we observed an erroneously low measured Tg value according to the presence of TgAb, and the degree showed positive correlation with concentration of TgAb [3, 4].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Data found in the literature indicated that in the presence of TgAb, values of Tg determined by immunoradiometric assay are usually lower than real values, even if the concentrations of TgAb are very low [5, 9, 19]. In previous reports, we observed an erroneously low measured Tg value according to the presence of TgAb, and the degree showed positive correlation with concentration of TgAb [3, 4].…”
Section: Discussionmentioning
confidence: 76%
“…It had been generally regarded that TgAb titer measured is below a clinical threshold will not be a significant influence on the Tg outcome; however, recent studies demonstrated that TgAb below the cut off can interfere the Tg outcome [19, 21]. Recently, Locsei et al also reported that the measured Tg value of patients serum can be influenced by mixing sheep TgAb in the reference range of TgAb concentration and deduced an equation estimating true Tg concentration using TgAb concentration in the same sample [9]. They proved the general concept of TgAb influence on the Tg measurement; however, their equation cannot be generally applied to clinical practice due to difference between sheep TgAb and human TgAb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, circulating Tg antibodies (TgAb) can confound conventional Tg assays and thereby prevent accurate measurement of Tg levels (2,3). TgAb therefore represent a significant clinical issue in thyroid cancer monitoring (4).…”
mentioning
confidence: 99%
“…These have been widely accepted management protocols [1] [2]. However, the presence of serum anti-Tg antibody (TgAb) may interfere with Tg measurement made by immunometric assay (IMA) or radioimmunoassay (RIA) methods and cause false results [3] [4] [5] [6]. In the presence of TgAb, IMA methods consistently underestimate serum Tg levels, while RIA methods generally overestimate serum TG levels [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%